Some remarks on the Urartian blind windows of Çavuştepe - Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Blind stone windows are one of the characteristic traits of Urartian architecture. Although they were a reinterpretation of a Mesopotamian feature, Urartian blind windows are distinguished by their unusual T-shape. This peculiarity was evidently determined by a practical purpose; since the window stood directly on the stone base of the wall and was surrounded by the mud-brick upper wall, the projecting sidepieces gave more structural stability to the wall blocks. The principal reason for the scarcity of specimens of this type of window in Urartian sites is probably that they were usually made out of mud-bricks, as in Mesopotamia.